BACHADONDAN TASHQARI HOMILADORLIKNI ANIQLASHDA UTTNING AHAMIYATI - To`raqulova Sevinch Sattorjon qizi; Xamidova M.A. (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Ectopic pregnancy remains one of the most dangerous emergencies in gynecology, posing a significant threat to a woman’s life and her reproductive potential. The primary objective of this study was to evaluate the diagnostic value of ultrasound examination (US) in the early detection of ectopic pregnancy. Within the framework of the methodology, a cohort of 30 reproductive-age women (18–40 years) with suspected ectopic pregnancy was examined using a two-stage protocol: transabdominal (TAUS) and transvaginal (TVUS) scanning, the results of which were compared with the clinical presentation and β-hCG levels. The results of the study demonstrated that TVUS has a significantly higher diagnostic accuracy (94%) compared to TAUS (68%), allowing for the early detection of the pathology in 86.7% of the patients. The timely application of high-resolution transvaginal ultrasound is the most important, safe, and highly effective tool for preventing severe complications and preserving the reproductive function of patients.